2015
DOI: 10.1002/elsc.201400151
|View full text |Cite
|
Sign up to set email alerts
|

Nerve tissue engineering using blends of poly(3‐hydroxyalkanoates) for peripheral nerve regeneration

Abstract: The only types of polyhydroxyalkanoates (PHAs) that have been explored for use in nerve regeneration are poly(3‐hydroxybutyrate), P(3HB), and poly(3‐hydroxybutyrate‐co‐3‐hydroxyhexanoate) (P(3HB‐co‐3HHx)). However, nerve regeneration induced by these PHAs is inferior to that of autologous nerve grafting. The aim of this work was to study novel PHA blends as resorbable biomaterials for the manufacture of nerve guidance conduits. PHA blend films with varying ratios of poly(3‐hydroxyoctanoate)/poly(3‐hydroxybutyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 39 publications
8
73
0
Order By: Relevance
“…Compression results on PGSm conduits showed an average Young's modulus of 3.2 MPa, similar to that of the native nerve (0.45 MPa) [44]. This similarity is further understood when compared with polycaprolactone (PCL), poly-L-lactide (PLLA) and poly(3-hydroxybutyrate) (P3HB), materials widely researched for peripheral nerve repair, with reported modulus values of 400 MPa, 668.4 MPa, 1160 MPa, respectively, far stiffer than that of the native nerve [25,[45][46][47][48]. Suture retention mechanical tests found PGSm conduits to have an average suture retention strength of 12.3 MPa, similar to the value reported for clinically used poly(tetrafluoroethylene) (as Gore-Tex vascular grafts), 23 MPa [49][50][51].…”
Section: Tablementioning
confidence: 60%
“…Compression results on PGSm conduits showed an average Young's modulus of 3.2 MPa, similar to that of the native nerve (0.45 MPa) [44]. This similarity is further understood when compared with polycaprolactone (PCL), poly-L-lactide (PLLA) and poly(3-hydroxybutyrate) (P3HB), materials widely researched for peripheral nerve repair, with reported modulus values of 400 MPa, 668.4 MPa, 1160 MPa, respectively, far stiffer than that of the native nerve [25,[45][46][47][48]. Suture retention mechanical tests found PGSm conduits to have an average suture retention strength of 12.3 MPa, similar to the value reported for clinically used poly(tetrafluoroethylene) (as Gore-Tex vascular grafts), 23 MPa [49][50][51].…”
Section: Tablementioning
confidence: 60%
“…An in‐depth study on the effect of the PHA blend fibre diameter on cell growth and differentiation of NG108‐15 neuronal and RN22 Schwann cells was carried out. The choice of this particular PHA blend was driven by our work that we have published earlier (Lizarraga‐Valderrama et al, ), in which this blend was shown to be the most biocompatible with respect to neuronal cells when compared with the widely commercialized PCL and other P(3HO)/P(3HB) blend compositions. The biodegradation product resulting from the breakdown of P(3HB), 3‐hydroxybutyric acid, is a known natural metabolite found in the human body, hence is expected to have minimal toxicity and immunogenic response (Newman & Verdin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Functional recovery was achieved following implantation of an oriented porous micropatterned Schwann cell seeded‐PHB nerve conduit into a 30 mm gap in sciatic nerves of rats . Blends of poly(3‐hydroxyoctanoate) (PHO) with PHB were able to support neuronal growth with the 25:75 blend film displaying tensile strength close to that of peripheral nerve . Peptide functionalized PHB/PHBV fibrous substrates resulted in enhanced SCs metabolic activity and proliferation.…”
Section: Other Te Applications: Potential Of Phasmentioning
confidence: 99%